Effect of Aquathol K on Hydrilla verticillata (L.F.) Royle - Mansor, Mashhor; Joyce , Joseph; Thyerr, Dan (1988)
A recently synthesized herbicide Aquathol K was tested on the water weed Hydrilla verticil. Results from the laboraoty tests indicated that Aquathol K with concentrations ranging from 1.0 mg/l to 2.0 mg/l can kill this weed. EVidently, 100% injury was achieved within 10 days for the plants treated with the highest concentration., 2. 0 mg/l of Aquathol K. The rate of 100% injury was recorded much slower with 1.0 mg/l. With lower concentration O.Smg/1 and 0.1 mg/l, 100% injury was never achieved within 25 days. Therefore, the herbicide was not very effective at lower concentrations.